Teachers' Practical Approach in Embedding Islamic Values in Students' Daily Activities - Juliani; Selpi Trianda Sari; Prilintan Gita Aulia; Yuni Siti Azwari; Rendy Prayoga (Journal of Contemporary Gender and Child Studies, 2024)
The instillation of Islamic values in students' daily activities plays a vital role in shaping their character and morality. Teachers, as primary educators, hold a highly strategic role in integrating Islamic values into the students' daily lives. This study aims to explore the practical approaches employed by teachers in instilling Islamic values within the school environment. This research adopts a qualitative descriptive approach using the library research method. The approach focuses on collecting data from various written sources to gain a deep theoretical understanding. Consequently, this study does not involve experiments or direct field data collection but emphasizes the analysis of relevant literature. The findings indicate that the approaches employed by teachers include setting examples through good morals, direct teaching of Islamic values across various subjects, and utilizing extracurricular activities and habituation in students' daily activities. Teachers also use everyday situations to connect events with moral lessons and Islamic teachings. Through these approaches, students can understand and internalize Islamic values in their lives, fostering the development of good character in line with Islamic teachings. The instillation of these values is not limited to cognitive aspects but also encompasses the affective and psychomotor dimensions of students' daily behavior.